Effect of Purple Crying Educational Program on Mothers’ Performance Regarding Prevention of Shaken Infant Syndrome - nada, mabroka; ElSobky, Fatma; Bahgat, Rahma (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Nurses and health care professionals caring for infants are in charge of teaching caregivers about the care of their infants. One of the most dangerous wounds that can happen during the initial one years of life is Shaken Infant Syndrome (SIS), a type of harsh head injury. The aim of the study Evaluate the effect of purple crying program on mothers’ performance regarding prevention of shaken infant syndrome .Subjects and method: quesi an experimental research design was used in the study. It was carried out at Pdiatric Department at Menoufia University Hospital and Benha University Hospital. Data were collect in a period of one years .A convenient sample composed of 50 mothers .Four tools were used to collect the data of this study: Personal and medical data assessment sheet , Knowledge Scale included crying and shaking ,Mothers practice about crying and Behavior Scales .The results revealed that after the application of educational programs, it was found that a significant improvement in knowledge, practice and behavior of mothers and also in following up after one month. Conclusion: the purple educational program had more effect on improvement of mothers’ knowledge, practice and behaviors regarding carrying and decrease infant shaking syndrome .Recommendations applying Shaken infant Syndrome educational Prevention Programs in hospitals should start early after birth immediately and should be reinforced with infant follow-up to improve information and interpret normal infant behaviors that can assist in abuse by caregivers. Applying Shaken infant Syndrome educational Prevention Programs in hospitals is important for the safety and quality of infant life.